2019
DOI: 10.1080/15548627.2019.1580105
|View full text |Cite
|
Sign up to set email alerts
|

The HGF-MET axis coordinates liver cancer metabolism and autophagy for chemotherapeutic resistance

Abstract: Notwithstanding the numerous drugs available for liver cancer, emerging evidence suggests that chemotherapeutic resistance is a significant issue. HGF and its receptor MET play critical roles in liver carcinogenesis and metastasis, mainly dependent on the activity of receptor tyrosine kinase. However, for unknown reasons, all HGF-MET kinase activity-targeted drugs have failed or have been suspended in clinical trials thus far. Macroautophagy/autophagy is a protective 'self-eating' process for resisting metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 165 publications
(132 citation statements)
references
References 58 publications
3
129
0
Order By: Relevance
“…According to previously established protocols (15), after two washes with ice-cold PBS, 5 Â 10 5 cells were resuspended in lysis buffer (25 mmol/L HEPES pH 7.5, 150 mmol/L NaCl, 0.25% Triton X-100, 0.25% NP-40, 0.25% CHAPS, 10% glycerol, and 1 Â protease inhibitor cocktail) on ice for 1.5 hours, and then centrifuged at 13,000 g for 15 minutes. The supernatants were precleared with 40 mL protein A/G-coupled agarose (sc-2003, Santa Cruz) for 1.5 hours and then incubated with 2 mg of the indicated antibodies, isotype control IgG (co-IgG)-conjugated beads, or 20 mL anti-Flag affinity gel (B23101, Bimake) for another 4 hours at 4 C. After three washes with lysis buffer, immunoprecipitates were boiled in 1 Â loading buffer for Western blot analysis.…”
Section: Immunoprecipitation and Western Blotmentioning
confidence: 99%
“…According to previously established protocols (15), after two washes with ice-cold PBS, 5 Â 10 5 cells were resuspended in lysis buffer (25 mmol/L HEPES pH 7.5, 150 mmol/L NaCl, 0.25% Triton X-100, 0.25% NP-40, 0.25% CHAPS, 10% glycerol, and 1 Â protease inhibitor cocktail) on ice for 1.5 hours, and then centrifuged at 13,000 g for 15 minutes. The supernatants were precleared with 40 mL protein A/G-coupled agarose (sc-2003, Santa Cruz) for 1.5 hours and then incubated with 2 mg of the indicated antibodies, isotype control IgG (co-IgG)-conjugated beads, or 20 mL anti-Flag affinity gel (B23101, Bimake) for another 4 hours at 4 C. After three washes with lysis buffer, immunoprecipitates were boiled in 1 Â loading buffer for Western blot analysis.…”
Section: Immunoprecipitation and Western Blotmentioning
confidence: 99%
“…Researchers have previously showed that HGF reduces susceptibility to alectinib by mainly restoring the downstream AKT and ERK pathways via MET activation, and the AKT-mTOR axis has important roles in the HGF/ MET pathway 12,34 . This research found that metformin selectively inhibited the abnormal phosphorylation of AKT, mTOR, ERK, P70S6K, and S6 in the presence of HGF but had no effect on the phosphorylation of MET, regardless of the absence or presence of alectinib.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these four genes were able to independently predict patient survival within the TCGA-LIHC dataset ( Figure 3C). This notion is supported by the failure of MET-targeting therapeutics to improve survival outcome that has been recently attributed, at least partly, to the ability of kinase-inhibited MET to promote cell survival via promoting autophagy [75]. Even though MET expression alone was not predictive, ERBB3, which contributes to the resistance to MET inhibition [76] displayed a high predictive potential ( Supplementary Table 1).…”
Section: Rtk Signaling and Angiogenesis Pathwaysmentioning
confidence: 94%